Present Status of Fish Seed Production at Chapai-Nawabgonj, Northern part of Bangladesh (Bangladesh Journal of Infectious Diseases, 2025)
Background: Chapai-Nawabgonj is located in the northern part of Bangladesh and is an important region for aquaculture, where fish seed production currently plays a vital role in both the local economy and sustainable fisheries development.Objective: The general objective of the study was to assess the present status of fish seed production in Chapai-Nawabgonj, a northern district of Bangladesh, to understand its current practices, challenges, and potential for development.Methodology: This study was designed as a descriptive and field-based survey to assess the current status of fish seed production. The research was conducted in various hatcheries and fish farms located in Chapai-Nawabgonj, situated in the northern region of Bangladesh. The study period spanned from January 2024 to December 2024, covering both peak and off-peak seasons of fish seed production. Data were collected through structured questionnaires, personal interviews with hatchery owners and workers, and direct observation of hatchery operations. Secondary data were also gathered from local fisheries offices and previous reports. The collected data were then analyzed to evaluate the production techniques, challenges faced, and potential areas for improvement.Results: The study revealed that fish seed production in Chapai-Nawabgonj is growing steadily and plays an important role in the local aquaculture sector. Most hatcheries are operating with limited technological advancement and face challenges such as inadequate training and financial support. Seasonal variations significantly impact seed availability, with shortages commonly observed during the off-season. Key problems identified include poor water quality, disease outbreaks, and lack of modern hatchery management practices. Overall, there is strong potential for enhanced fish seed production through better training, infrastructure, and policy support.Conclusion: In conclusion, fish seed production in Chapai-Nawabgonj holds significant potential for growth and it requires improved technical support, training, and infrastructure.Bangladesh Journal of Infectious Diseases, June 2025;12(1):125-133